HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA GURU PPPK - Salsalbillah Ramadhanti; Doddy Hendro Wibowo (Bajang Institute, 2023)
The teacher plays a crucial role in realizing the goals and performing the fundamental functions of the school institution. Highlighting the different rights but shared duties and responsibilities between civil servant teachers (PNS) and non-civil servant teachers (PPPK), this research is conducted with the aim of investigating the relationship between emotional intelligence and Organizational Citizenship Behavior (OCB) among PPPK teachers. The participants in this study consisted of 94 PPPK teachers located in Semarang Regency, gathered through incidental sampling techniques. Two psychological scales were employed in this research: the OCB measurement tool and the emotional intelligence measurement tool. The results of the correlational analysis using Pearson Correlation indicated a significance level of 0.00 (p<0.05), which means that there is a positive relationship between emotional intelligence and OCB among PPPK teachers.